Compulsive Internet Use Scale: Psychometric Properties and Associations With Sleeping Patterns, Mental Health, and Well-Being in Lithuanian Medical Students During the Coronavirus Disease 2019 Pandemic - Milasauskiene, Egle; Burkauskas, Julius; Podlipskyte, Aurelija; Király, Orsolya; Demetrovics, Zsolt; Ambrasas, Laurynas; Steibliene, Vesta (Frontiers in Psychology, 2021)
The increase in problematic Internet use (PIU) among medical students and resident doctors during COVID-19 pandemic may be leading to significant impairments in everyday functioning, including sleeping patterns, anxiety, depressive symptoms and overall well-being. The Compulsive Internet Use Scale (CIUS) has been developed to assess the severity of PIU, however, it has not been elucidated whether this scale is also applicable to medical students and resident doctors. We aimed to explore psychometric properties of the Lithuanian version of the CIUS. Our secondary aim was to evaluate PIU prevalence among medical students and resident doctors, and to examine associations between mental health symptoms and PIU during COVID-19 pandemic. Methods: A total of 524 medical students and resident doctors (78.60% female, mean age 24 [SD 3] years old) participated in an online survey. Participants completed the CIUS, Pittsburgh sleep quality index, Patient Health Questionnaire-9, Generalised Anxiety Disorder Assessment-7, and the World Health Organization – Five Well-Being Index. Results: The Lithuanian version of the CIUS had an excellent internal consistency of α = 0.904 for the sample of medical students and resident doctors. The confirmatory factor analysis suggested one-factor model and indicated a satisfactory fit (root mean square error of approximation [RMSEA] = 0.071, RMSEA 90%CI = 0.062–0.081; comparative fit index [CFI] = 0.945; normed fit index [NFI] = 0.926; Tucker-Lewis Index [TLI] = 0.930; χ2/df = 3.67). The prevalence of PIU was calculated at 31.7% of all participants with the most prevalent online behaviors being social media use (90.1%), online shopping (15.6%), online gaming/gambling (11.3%). Students with PIU reported significantly lower academic achievements during the 6-month period (p = 0.004), as well as more severe depressive and anxiety symptoms, worsened sleep quality and lower well-being (p’s < 0.05). Both, during workdays and weekend, students spent more time online than resident doctors (p’s < 0.001). Conclusions: The Lithuanian version of the CIUS is reliable and valid instrument for evaluating severity of PIU symptoms in medical student’s population. One third of medical students and resident doctors reported symptoms of PIUs during the COVID-19 period, which were associated with worsened mental health and everyday functioning.